2014
DOI: 10.1016/j.asr.2013.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Stark broadening of Ar XV lines. Strong collision and quadrupolar potential contributions

Abstract: We present in this paper electron impact broadening for six Ar XV lines using our quantum mechanical formalism and the semiclassical perturbation one. Additionally, our calculations of the corresponding atomic structure data (energy levels and oscillator strengths) and collision strengths are given as well. The lines considered here are divided into two sets: a first set of four lines involving the ground level: 1s 2 2s 2 1 S 0 − 1s 2 2snp 1 P o 1 where 2 ≤ n ≤ 5 and a second set of two lines involving excited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…Av stands for a Boltzmann thermal average. With the advent of accurate atomic structure and S matrix codes, such impact quantum calculations have been given a new life [6,7], and are most often in good agreement with other calculations. A very efficient calculation has been proposed starting from Equation (2), using a Bethe-Born approximation [8] for evaluating inelastic cross sections.…”
Section: Impact Broadeningmentioning
confidence: 86%
See 1 more Smart Citation
“…Av stands for a Boltzmann thermal average. With the advent of accurate atomic structure and S matrix codes, such impact quantum calculations have been given a new life [6,7], and are most often in good agreement with other calculations. A very efficient calculation has been proposed starting from Equation (2), using a Bethe-Born approximation [8] for evaluating inelastic cross sections.…”
Section: Impact Broadeningmentioning
confidence: 86%
“…Semiclassical calculations may be brought closer to quantum widths, e.g., by a refined calculation of the minimum impact parameter allowing the use of a classical path [14]. Surprisingly, quantum widths of Li-like and boron-like ions often show a worse agreement with experiments than semiclassical calculation, thus calling for further calculations and analysis [7,15]. As an example of such, more recent quantum calculations [15] are in fairly good agreement with experiments [15].…”
Section: Impact Broadeningmentioning
confidence: 99%
“…In the present work, the calculations of atomic data are computed by the sequence of UCL (University College, London) atomic packages (SUPERSTRUCTURE (Eissner et al, 1974)/DW (Eissner, 1998)/JAJOM (Saraph, 1978)). In Elabidi et al (2014); ; Aloui et al (2018Aloui et al ( , 2019, the authors adapted these packages to provide Stark broadening data for several argon lines missing in the literature. This method gave acceptable results.…”
Section: Introductionmentioning
confidence: 99%
“…The World Commission on Dams (International Commission on Large Dams, 2003) reported that approximately 50,000 large dams (i.e., with heights more than 15 m) were operational worldwide with a total storage capacity of about 7,000 billion cubic meters (BCM) (Chao et al, 2008;Lehner et al, 2011;Postel et al, 1996;Vörösmarty & Sahagian, 2000). More than 40% of global river discharge is intercepted by the 663 largest reservoirs in the world (Vörösmarty et al, 1997). The total global reservoir storage capacity is one sixth of the annual global river discharge (Hanasaki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The primary use of dams and reservoirs in India includes irrigation, hydropower, and flood control. Surface water storage and water management activities affect the terrestrial water and energy cycles by increasing total water use, which in turn alter the partitioning of water and energy budgets over irrigated agricultural land, and by modifying streamflow seasonality through reservoir operations Haddeland et al, 2007;Hanasaki et al, 2006;Nilsson et al, 2005;Vörösmarty et al, 1997;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%